Weber, re-enchantment and social futures - Lee, R.L.M. (SAGE Publications (UK and US), 2010)
Weber's portrayal of modern society as disenchanted was implicitly a way of considering the rationalization of social futures. These are futures derived from empiricist understandings of world mastery and regarded as devoid of mystery. Yet he devoted some writings to charisma and magic that were incongruent with his focus on rationality, suggesting alternative social futures that highlight mysteries for the recovery of meaning. By examining these writings in the context of his critique of modernity, it is possible to draw out some of his ideas on re-enchantment as the key to understanding alternative social futures.